Pendugaan Biomasa di Atas Tanah di Ekosistem Hutan Primer dan Hutan Bekas Tebangan (Studi Kasus Hutan Dusun Aro, Jambi) - Tresnawan, Hamdan; Rosalina, Upik (Institut Pertanian Bogor (IPB University), 2002)
Biomass studies using combination of destructive and non-destructive sampling were conducted in the tropical rain forest od Dustum Aro, Jambi, In non-destructive sampling, biomass densiry was estimated using algometric equation from Brawn (1997) mainly for trees with diameter at breast height greater than 5 cm.